Answer:
D
Step-by-step explanation:
Let x be Bill’s scores.
Let y be Theo’s scores.
x + y = 90
x² = y
Solve for x in the second equation.
x = √y
Put x as √y in the first equation and solve for y.
√y + y = 90
√y = 90 - y
y = (90 - y)²
y = - y² - 180y - 8100
0 = -y² - 181y - 8100
0 = (-y+81)(y-100)
-y+81=0
y = 81
y - 100 = 0
y = 100
100 does not work if we plug in to check, so y is 81.
y = 81
Put y as 81 in the first equation and solve for x.
x + 81 = 90
x = 9
Bill scored 9 goals and Theo scored 81.
Answer:
The amount that came is ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
Step-by-step explanation:
The computation is shown below:
According to the question, it is mentioned that
Multiply 4 by ![-5\frac{2}{3}](https://tex.z-dn.net/?f=-5%5Cfrac%7B2%7D%7B3%7D)
First open the equation in a fraction it would be ![\frac{-17}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-17%7D%7B3%7D)
Now multiplied the above fraction by a 4
That gives the result of ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
Hence, the amount that came is ![\frac{-68}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-68%7D%7B3%7D)
We simply multiply the 4 with the given fraction
Thus the above represents the simplest form of the fraction
Answer:
She pays $566.10
Step-by-step explanation:
The mattress store marks a mattress up 100%. 100% of $225 is 225. We add 225 to 225 and get 510. Therefore, the store sells the mattress for $510 without tax. When Cassie buys the mattress, we have to add 11% tax. We change 11% to 0.11 and multiply that by the selling price (510). We get 56.10, so that is the tax. We add the tax to the selling price and get $566.10. Cassie pays $566.10 for the mattress.
I hope this helped and please mark me as brainliest!
Answer:
Option A) Circle.
Step-by-step explanation:
We are given the equation:
![(x - 3)^2 + (y - 12)^2 = 25](https://tex.z-dn.net/?f=%28x%20-%203%29%5E2%20%2B%20%28y%20-%2012%29%5E2%20%3D%2025)
A general equation of the circle is of the form:
![(x-h)^2 + (y-k)^2 = r^2](https://tex.z-dn.net/?f=%28x-h%29%5E2%20%2B%20%28y-k%29%5E2%20%3D%20r%5E2)
where (h,k) is the center of the circle and r is the radius of circle.
Comparing the two equations, we get,
![(h,k) = (3,12)\\r = \sqrt{25} = 5](https://tex.z-dn.net/?f=%28h%2Ck%29%20%3D%20%283%2C12%29%5C%5Cr%20%3D%20%5Csqrt%7B25%7D%20%3D%205)
Thus, the given equation is equation of a circle centered at (3,12) and of radius 5 units.